Ketimpangan Produktivitas Tenaga Kerja Antar Kabupaten/Kota di Provinsi Bengkulu - Armelly, Armelly; Ekaputri, Retno Agustina; Febriani, Ratu Eva; Novi Tri (Universitas Bengkulu, 2023)
The purpose of this study is to analyze the condition of inequality and comparison between districts in Bengkulu Province. The study used data from Badan Pusat Statistik related to employment data for 10 districts and Bengkulu Province for 3 years, with the research methods: Williamson Index analysis, deskriptive analysis and elasticity of productivity analysis. The results show that there is an inequality in labor productivity between districts in Bengkulu Province during 2018 to 2020 which is indicated by IW value of 0,40-0,47. The range between productivity values that is getting bigger in 2020 indicates an increasing productivity inequality. Keywords: labor productivity; inequality